Angular analysis and branching fraction measurement of the decay B0 → K*0μ+μ- - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; et al. (ELSEVIER, 2013)
The angular distributions and the differential branching fraction of the decay B-0 -> K*(892)(0)mu(+)mu(-) are studied using a data sample corresponding to an integrated luminosity of 5.2 fb(-1) collected with the CMS detector at the LHC in pp collisions at root s = 7 TeV. From more than 400 signal decays, the forward-backward asymmetry of the muons, the K*(892)(0) longitudinal polarization fraction, and the differential branching fraction are determined as a function of the square of the dimuon invariant mass. The measurements are in good agreement with standard model predictions. (C) 2013 CERN. Published by Elsevier B.V. All rights reserved.
Keywords: CMS; Physics; RARE; Astronomy & Astrophysics